A new electro–hydraulic triaxial tyre test facility for low–frequency rolling tyre dynamics. (5th August 2014) - Dunn, J.W.; Olatunbosun, O.A.
The existing triaxial tyre test rig at the Automotive Engineering Centre, University of Birmingham, was recently replaced by a new electro–hydraulically driven facility which has provided a number of improvements over the previous electromagnetically driven facility. This paper describes the main design features of the new facility, and its advantages over the old facility are highlighted, particularly the possibility of simulating vehicle boundary conditions by programmed control of the electro–hydraulic actuators. A system model for extracting tyre modal parameters from the test data is derived, and some sample results are presented to illustrate the accuracy of the model.